2021
DOI: 10.23922/jarc.2020-095
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Colorectal Cancer Surgery for ≥ 85-year-old Patients in Our Hospital: Retrospective Comparison of Short- and Long-term Outcomes with Younger Patients

Abstract: Objectives: To evaluate future problems in colorectal cancer surgery for elderly patients. Methods: We conducted a retrospective review of patients receiving colorectal cancer surgery in our hospital from January 2010 to December 2018. Patients were divided into the !85-year-old patient group and the younger patient group. We compared patient backgrounds, surgical outcomes (surgical procedure, reduction of lymph node dissection range, operative duration, and blood loss), postoperative short-term outcomes (mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
2
1
1
Order By: Relevance
“…Although univariate analysis showed a lower proportion of elderly patients (≥75) achieving TO, this factor was not significant in multivariable analysis. These results contradict Fukuoka and colleagues’ previous findings, who reported that patients older than 85 were more prone to postoperative complications, particularly pneumonia and thromboembolism [ 20 ]. However, the age threshold used in our study was significantly different, so the findings may not be entirely consistent.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although univariate analysis showed a lower proportion of elderly patients (≥75) achieving TO, this factor was not significant in multivariable analysis. These results contradict Fukuoka and colleagues’ previous findings, who reported that patients older than 85 were more prone to postoperative complications, particularly pneumonia and thromboembolism [ 20 ]. However, the age threshold used in our study was significantly different, so the findings may not be entirely consistent.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent research has highlighted the crucial role of TO in ensuring the safer delivery of healthcare services [ 17 , 18 , 19 ]. TO is defined as a combination of different outcome measures that can provide greater value compared to individual parameters when conducting clinical audits of surgical treatments, according to Fukuoka A and colleagues [ 20 ]. Our study showed that only 52.5% of patients undergoing elective surgery for colorectal cancer achieved TO.…”
Section: Discussionmentioning
confidence: 99%
“…Если для пациентов молодого и пожилого возрастов объем радикального хирургического лечения колоректального рака определен и рекомендован в ведущих онкологических руководствах [1], то вопрос об объеме лимфодиссекции в старческом возрасте остается не решенным. По данным A. Fukuoka et al, выполнение ограниченной лимфодиссекции пациентам старшей возрастной категории не ведет к ухудшению общей безрецидивной выживаемости [9]. В противовес данному мне-нию M. Takahashi et al указывают на необходимость выполнения лимфодиссекции в объеме D3 для пациентов ≥80 лет с колоректальным раком как на оптимальный объем хирургического вмешательства, улучшающий отдаленные результаты лечения, по сравнению с лимфодиссекцией D2 (HR 0,59; CI 0,41-0,83, p < 0,001) [10].…”
Section: Discussionunclassified
“…In a retrospective review, Asako Fukuoka et al [24] evaluated the surgical outcomes, postoperative short-term outcomes and prognosis of 1240 patients (1131/91.2%, <85 years old) in order to better select elderly patients for robotic surgery. ASA scores were significantly poorer in the elderly group; on the contrary, the rate of reduction of lymph node dissection range, overall morbidity and respective frequencies of pneumonia and thromboembolism were significantly higher in the elderly.…”
Section: Robotic Colorectal Surgery In the Elderlymentioning
confidence: 99%